2014
DOI: 10.1371/journal.pone.0110888
|View full text |Cite|
|
Sign up to set email alerts
|

Integrative Data Mining Highlights Candidate Genes for Monogenic Myopathies

Abstract: Inherited myopathies are a heterogeneous group of disabling disorders with still barely understood pathological mechanisms. Around 40% of afflicted patients remain without a molecular diagnosis after exclusion of known genes. The advent of high-throughput sequencing has opened avenues to the discovery of new implicated genes, but a working list of prioritized candidate genes is necessary to deal with the complexity of analyzing large-scale sequencing data. Here we used an integrative data mining strategy to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…41,42 Further evidence that the pathogenicity of the variants in RYR3 probably contribute to the arthrogryposis phenotype comes from bioinformatics studies; Abath Neto et al performed a computational data-mining study based on gene ontology (GO) terms, human phenotype ontology (HPO) terms, pathways, complexes, and protein motifs, and they found that RYR3 is highly ranked as one of the congenital myopathy genes. 43 Mutations in RYR1, a paralog of RYR3, were shown to cause MYOM2 is specifically expressed in the heart and skeletal muscle, the cardiac and arthrogryposis findings can be potentially explained by loss of function (LoF) mutation of MYOM2. Further evidence for probable pathogenicity comes from functional studies that showed that MYOM2 interacts directly with dysferlin, which plays an essential role in sarcolemma repair; abnormalities of dysferlin cause a wide variety of myopathies called dysferlinopathies.…”
Section: Human F Q a R A K L Rhesus F Q A R A K L Mouse F Q A R A K Lmentioning
confidence: 99%
“…41,42 Further evidence that the pathogenicity of the variants in RYR3 probably contribute to the arthrogryposis phenotype comes from bioinformatics studies; Abath Neto et al performed a computational data-mining study based on gene ontology (GO) terms, human phenotype ontology (HPO) terms, pathways, complexes, and protein motifs, and they found that RYR3 is highly ranked as one of the congenital myopathy genes. 43 Mutations in RYR1, a paralog of RYR3, were shown to cause MYOM2 is specifically expressed in the heart and skeletal muscle, the cardiac and arthrogryposis findings can be potentially explained by loss of function (LoF) mutation of MYOM2. Further evidence for probable pathogenicity comes from functional studies that showed that MYOM2 interacts directly with dysferlin, which plays an essential role in sarcolemma repair; abnormalities of dysferlin cause a wide variety of myopathies called dysferlinopathies.…”
Section: Human F Q a R A K L Rhesus F Q A R A K L Mouse F Q A R A K Lmentioning
confidence: 99%
“…In addition, an integrated data-mining strategy ranking genes with known or potential importance for skeletal muscle has previously highlighted RYR3 as a candidate gene for CMs, myotonic syndromes and ion channel muscle diseases [18]. Some of the other candidates from Neto et al [18] are now known disease genes, i.e. MYO18B and CASQ1.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and phenotypic heterogeneity is a common source of uncertainty in the diagnosis of several inherited musculoskeletal disorders, as well as in investigating their etiology. High-throughput sequencing can help outline the underlying genomic features in these disorders through variant discovery in many genes simultaneously [38,39], but the ultra-high output poses limits to its practicability as a diagnostic tool [24][25][26][27][28][29]. For diagnostic purposes, full sequencing of a panel of firmly established gene candidates can be adequately handled with resequencing arrays, which have already been successfully applied in clinical trials [33].…”
Section: Discussionmentioning
confidence: 99%